2003
DOI: 10.1177/000348940311201113
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Idiopathic Sudden Sensorineural Hearing Loss with Antiviral Therapy: A Prospective, Randomized, Double-Blind Clinical Trial

Abstract: A subclinical viral labyrinthitis has been postulated in the literature to elicit idiopathic sudden sensorineural hearing loss (ISSHL). An etiologic role for the herpes family is assumed. Corticosteroids possess a limited beneficial effect on hearing recovery in ISSHL. In this study, we evaluated the therapeutic value of the antiherpetic drug acyclovir (Zovirax) on hearing recovery in 91 patients with ISSHL who received prednisolone in a prospective, randomized, double-blind, placebo-controlled, multicenter tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0
6

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(76 citation statements)
references
References 20 publications
2
68
0
6
Order By: Relevance
“…Although we observed similar efficacy of oral and intratympanic treatments overall, our subgroup analyses suggested that certain subgroups might achieve greater benefit from one treatment than the other. A number of studies have considered combination therapy using oral plus intratympanic steroid (or other treatments) administered concurrently for primary hearing loss treatment [28][29][30][31] or the applicability of intratympanic steroid for salvage treatment in patients who have failed to regain hearing with oral steroid treatment. [32][33][34][35][36][37] None of these studies has been conclusive due to problems of study design, limited sample size, or both.…”
Section: Commentmentioning
confidence: 99%
“…Although we observed similar efficacy of oral and intratympanic treatments overall, our subgroup analyses suggested that certain subgroups might achieve greater benefit from one treatment than the other. A number of studies have considered combination therapy using oral plus intratympanic steroid (or other treatments) administered concurrently for primary hearing loss treatment [28][29][30][31] or the applicability of intratympanic steroid for salvage treatment in patients who have failed to regain hearing with oral steroid treatment. [32][33][34][35][36][37] None of these studies has been conclusive due to problems of study design, limited sample size, or both.…”
Section: Commentmentioning
confidence: 99%
“…In the treatment of SSNHL, a relatively frequent disease, the gold standard Turk Arch Otolaryngol 2014; 52: is steroid therapy (1-3). In addition, many methods, including rheological agents, contrast media, vasodilators, antiviral agents, and hyperbaric oxygen therapy, are still tried (4)(5)(6)(7)(8). Some of these have lost their importance, and some methods, such as hyperbaric oxygen therapy, are being investigated (18).…”
Section: Discussionmentioning
confidence: 99%
“…However, Tucci et al (5) compared valacyclovir and prednisolone therapies in their study and could not suggest that antiviral treatment was superior to steroid treatment. Similarly, in the study conducted by Westerlaken et al (6), they compared acyclovir and prednisolone and found no superiority of these treatments over steroid treatment.…”
Section: Introductionmentioning
confidence: 94%
“…Dado que las tres hipótesis fundamentales en la génesis de la sordera brusca son la viral, la vascular y la inmunológica, cabe esperar que los tratamientos con antivirales, vasodilatadores y corticoides, sean aquellos con los que mejores respuestas se consigan. Hemos encontrado múltiples estudios en los que el uso de aciclovir y valaciclovir, aciclovir solo o famciclovir, no han resultado beneficiosos 19,[21][22][23][24] . En otros, la asociación del aciclovir con la prednisona, sí que ha mostrado mejoría 25 .…”
Section: Discussionunclassified